1990
DOI: 10.1271/bbb1961.54.2257
|View full text |Cite
|
Sign up to set email alerts
|

L-sorbose dissimilation in 2-keto-L-gulonic acid-producing mutant UV10 derived from Gluconobacter melanogenus IFO 3293.

Abstract: During the fermentation of 2-keto-L-gulonic acid (2KGA) from L-[U-14C]sorbose by the 2KGA-producing mutant UV10, derived from G. melanogenus IFO 3293, 40% of the metabolized substrate was converted to l4CO2. The CO2 evolved was mainly via the pentose phosphate pathway and partly via the intermediates such as L-sorbosone or the by-products of 2KGAformation. CO2 evolution from 2KGAwas not observed. 2KGA is an important intermediate in the synthesis of L-ascorbic acid (vitamin C). Various approaches to produce 2K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Strain U13 is a derivative of UV10 and exhibits higher SDH activity than UV10. In strains exhibiting weaker SDH activities, there is stronger carbon flow toward final assimilation of the substrate to CO 2 , mainly via the pentose cycle, as reported previously (21).…”
Section: Formation Of 2kga From L-sorbosone L-sorbose and Dsorbitolsupporting
confidence: 80%
See 1 more Smart Citation
“…Strain U13 is a derivative of UV10 and exhibits higher SDH activity than UV10. In strains exhibiting weaker SDH activities, there is stronger carbon flow toward final assimilation of the substrate to CO 2 , mainly via the pentose cycle, as reported previously (21).…”
Section: Formation Of 2kga From L-sorbosone L-sorbose and Dsorbitolsupporting
confidence: 80%
“…Most of the carbon loss was found to be in the form of CO 2 gas that evolved mainly from the pentose phosphate pathway in the cytoplasm (cSNDH in Fig. 1) (21). In addition, we found that Acetobacter liquefaciens (formerly G. melanogenus) IFO 12258 converted L-sorbosone to 2KGA stoichiometrically (21a) and contained the membrane-bound SNDH.…”
mentioning
confidence: 88%
“…This involves an initial phosphorylation of glucose or gluconate to glucose-6-phosphate or 6-phosphogluconate, respectively, and subsequent metabolism of these intermediates via the PPP or EDP (29,31,40). The fact that the majority of the carbon source is incompletely oxidized to ketoacids as products rather than being metabolized via the PPP and EDP results in very low biomass yields, in the range of 0.10 g cell dry weight (CDW) per g of glucose consumed (29).…”
Section: And N-formyl-1-amino-1-deoxy-d-sorbitolmentioning
confidence: 99%
“…In either case, an NAD(P)H-dependent reductase catalyzing the reduction of L-sorbose or L-sorbose-1-phosphate is essential for L-sorbose utilization in these microorganisms (8). The metabolic pathways of D-sorbitol, Lsorbose, and their metabolites in Gluconobacter strains have been studied previously (9,20,22), and these C sources were shown to be utilized through a nonphosphorylating pathway; however, no transcriptional analysis has yet been performed.…”
mentioning
confidence: 99%